Gambaran Job crafting pada Mahasiswa yang Memiliki Peran Ganda - Madinatul I. Hidayah; Marco Kemalleka; Salsabila A. P. Nastiti; Dewi Fatmasari Edy (Flourishing Journal, 2024)
College students as individuals who are in the early adulthood phase, have a lot of desire to explore themselves through a series of learning processes in lectures and also organizational activities. Student involvement in organizational activities means students have multiple roles. Students playing multiple roles is a phenomenon that is most often encountered in the campus environment. In living life as a student and organizer, of course there are many challenges and work that must be faced and resolved. Sometimes this dual role can also have various impacts on students. Therefore, by looking at the roles and responsibilities of each role, the researcher wants to reveal in descriptive form a picture of job crafting among students with multiple roles. Data collection method using semi-structured interviews. The criteria for interviewees are students who join organizations as a second role. This research involved three sources to be interviewed. The analysis technique used uses thematic analysis techniques to identify themes in the data. The result is that students have 4 aspects of job crafting, namely: increasing structural job resources, increasing challenging job demands, increasing social job resources, decreasing hindering job demands. Each aspect has a more detailed sub-theme. AbstrakMahasiswa sebagai individu yang berada pada tahap fase dewasa awal, memiliki banyak keinginan untuk mengeksplorasi diri melalui serangkaian proses pembelajaran yang ada di perkuliahan dan juga kegiatan organisasi. Keterlibatan mahasiswa dalam kegiatan organisasi membuat mahasiswa memiliki peran ganda. Mahasiswa berperan ganda merupakan fenomena yang paling sering dijumpai dalam lingkungan kampus. Dalam menjalani kehidupan sebagai mahasiswa dan organisator tentunya banyak tantangan dan pekerjaan yang harus dihadapi dan diselesaikan. Terkadang peran ganda ini juga dapat menimbulkan berbagai dampak pada mahasiswa. Oleh karena itu dengan melihat peran dan tanggung jawabnya masing-masing peran, peneliti ingin mengungkap dalam bentuk deskriptif gambaran job crafting pada mahasiswa berperan ganda. Metode pengambilan data dengan wawancara semi terstruktur. Kriteria narasumber adalah mahasiswa yang mengikuti organisasi sebagai peran kedua. Penelitian ini melibatkan tiga narasumber untuk diwawancarai. Teknik analisis yang digunakan menggunakan teknik analisis tematik untuk mengidentifikasi tema dalam data. Hasilnya adalah mahasiswa memiliki 4 aspek dalam job crafting, yaitu: increasing structural job resources, increasing challenging job demands, increasing social job resources, decreasing hindering job demands. Setiap aspek tersebut memiliki sub tema yang lebih merinci.